Migrant Street Vendors in Italy: A History of Irregularized Labour and People - Ragone, Marianna; Avallone, Gennaro (Calitatea Vieții, 2022)
Migrant street workers are removed from urban spaces in the Italian cities where they work, because of municipal and police decisions. The methodology followed in this research oriented to understand migrant street vending in Italy is constructivist and mixed, qualitative, and quantitative. The hypothesis that is supported by this article is that the political and racist restrictions imposed on immigrant street vendor workers produce a process of irregularisation that jeopardises their chances of renewing their residence permit or gaining access to citizenship. The paper then discusses how forms of racialization are reproduced through systems of irregularisation, and introduces the concept of democratic racialization to understand how racialisation is reproduced, consolidated, and normalised by democratic instruments. The paper ends with suggestions for future research to collect data on police decisions and actions against foreign street workers.